Pharmacokinetics, safety, and efficacy of cedirogant from phase I studies in healthy participants and patients with chronic plaque psoriasis - Mohamed‐Eslam F. Mohamed; Yuli Qian; Ronilda D'Cunha; Teresa Sligh; Laura K. Ferris; Ann Eldred; Gweneth F. Levy; Shuai Hao; Shashikanth Gannu; David G. Rizzo; Wei Liu; Sasha Jazayeri; et al. (Wiley, 2024)
Abstract Cedirogant is an inverse agonist of retinoic acid‐related orphan receptor gamma thymus (RORγt) developed for the treatment of moderate to severe chronic plaque psoriasis. Here, we report the results from two phase I studies in which the pharmacokinetics (PK), safety, and efficacy of cedirogant in healthy participants and patients with moderate to severe chronic plaque psoriasis were evaluated. The studies consisted of single (20-750 mg) and multiple (75-375 mg once‐daily [q.d.]) ascending dose designs, with effect of food and itraconazole on cedirogant exposure also evaluated. Safety and PK were evaluated for both healthy participants and psoriasis patients, and efficacy was assessed in psoriasis patients. Following single and multiple doses, cedirogant mean terminal half‐life ranged from 16 to 28 h and median time to reach maximum plasma concentration ranged from 2 to 5 h across both populations. Cedirogant plasma exposures were dose‐proportional after single doses and less than dose‐proportional from 75 to 375 mg q.d. doses. Steady‐state concentrations were achieved within 12 days. Accumulation ratios ranged from approximately 1.2 to 1.8 across tested doses. Food had minimal effect and itraconazole had limited impact on cedirogant exposure. No discontinuations or serious adverse events due to cedirogant were recorded. Psoriasis Area and Severity Index (PASI) and Self‐Assessment of Psoriasis Symptoms (SAPS) assessments demonstrated numerical improvement with treatment of cedirogant 375 mg q.d. compared with placebo. The PK, safety, and efficacy profiles of cedirogant supported advancing it to phase II clinical trial in psoriasis patients.